Inference of selective forces on house mouse genomes during secondary contact in East Asia - Fujiwara, Kazumichi; Kubo, Shunpei; Endo, Toshinori; Takada, Toyoyuki; Shiroishi, Toshihiko; Suzuki, Hitoshi; Osada, Naoki (Genome Research, 2024)
The house mouse (Mus musculus), which is commensal to humans, has spread globally via human activities, leading to secondary contact between genetically divergent subspecies. This pattern of genetic admixture can provide insights into the selective forces at play in this well-studied model organism. Our analysis of 163 house mouse genomes, with a particular focus on East Asia, revealed substantial admixture between the subspecies castaneus and musculus, particularly in Japan and southern China. We revealed, despite the different level of autosomal admixture among regions, that all Y Chromosomes in the East Asian samples belonged to the musculus-type haplogroup, potentially explained by genomic conflict under sex-ratio distortion owing to varying copy numbers of ampliconic genes on sex chromosomes, Slx and Sly. Our computer simulations, designed to replicate the observed scenario, show that the preferential fixation of musculus-type Y Chromosomes can be achieved with a slight increase in the male-to-female birth ratio. We also investigated the influence of selection on the posthybridization of the subspecies castaneus and musculus in Japan. Even though the genetic background of most Japanese samples closely resembles the subspecies musculus, certain genomic regions overrepresented the castaneus-like genetic components, particularly in immune-related genes. Furthermore, a large genomic block (∼2 Mbp) containing a vomeronasal/olfactory receptor gene cluster predominantly harbored castaneus-type haplotypes in the Japanese samples, highlighting the crucial role of olfaction-based recognition in shaping hybrid genomes.